2021
DOI: 10.1155/2021/2506286
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Data-Driven Photovoltaic Power Generation System Based on Deep Reinforcement Learning

Abstract: Aiming at the problem of fault diagnosis of the photovoltaic power generation system, this paper proposes a photovoltaic power generation system fault diagnosis method based on deep reinforcement learning. This method takes data-driven as the starting point. Firstly, the compressed sensing algorithm is used to fill the missing photovoltaic data and then state, action, strategy, and return functions from the environment. Based on the interaction rules and other factors, the fault diagnosis model of the photovol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…One method [47] can detect two types of faults (short-circuit fault, mismatch faults), and six methods [44,45,48,49,51,52] can detect only one type of fault (open-circuit fault, arc fault, mismatch faults, short-circuit fault, arc fault, mismatch faults respectively). Regarding the accuracy of fault detection, nine methods [41,42,45,[47][48][49][50][51]53] show an accuracy of more than 95%, while one method [46] shows fluctuating accuracy depending on the type of the fault (89.6-98%). Finally, only two methods [43,50] provide information about their computational cost, it has to be noted though that the method presented in [50] provides data only for its execution time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One method [47] can detect two types of faults (short-circuit fault, mismatch faults), and six methods [44,45,48,49,51,52] can detect only one type of fault (open-circuit fault, arc fault, mismatch faults, short-circuit fault, arc fault, mismatch faults respectively). Regarding the accuracy of fault detection, nine methods [41,42,45,[47][48][49][50][51]53] show an accuracy of more than 95%, while one method [46] shows fluctuating accuracy depending on the type of the fault (89.6-98%). Finally, only two methods [43,50] provide information about their computational cost, it has to be noted though that the method presented in [50] provides data only for its execution time.…”
Section: Resultsmentioning
confidence: 99%
“…The method is based in principal component analysis (PCA) that used data from I-V curves to detect faults with significant accuracy. Finally, Dai et al [53] suggested a deep reinforcement learning-based PVS fault detection technique. The starting premise for this approach is data-driven.…”
Section: Fault Detection Algorithmsmentioning
confidence: 99%
“…Increasing the number of convolution layer and sampling layer will increase the network complexity and increase the network learning time. [4] In order to adapt to one-dimensional input data, the convolution kernel is set as one-dimensional convolution kernel. Different convolution kernels extract different features of the input data, and then through the dimensionality reduction operation of the sampling layer, the output nodes of the sampling layer are greatly reduced, and the network computation is also reduced, but the output of the sampling layer cannot be used as the classification result, It is necessary to connect the full connection layer and the Softmax regression layer behind the sampling layer to obtain the probability corresponding to various states.…”
Section: Input Of Prediction Modelmentioning
confidence: 99%
“…LM method can correct the error of the algorithm. The algorithm always follows the direction of negative gradient during the iteration, and searches the error in the ascending direction, and finds the appropriate control factor u through repeated iteration, thus solving the problem of the lower bound in the network (4).…”
Section: Improvement Of Bp Neural Network Prediction Modelmentioning
confidence: 99%
“…Fault detection problem in GTPS is often considered as a classification challenge. 36 However, the realm of DRL is chiefly designed to address sequential decision-making predicaments. Drawing inspiration from prior references, this study reframes inverter fault diagnosis as a form of deduction game.…”
Section: Working With Td3pg Control Agentsmentioning
confidence: 99%